MENUMBUHKAN BUDAYA MEMBACA SEJAK DINI MELALUI POJOK LITERASI PAUD DI DESA WARUNGDOWO KECAMATAN POHJENTREK KABUPATEN PASURUAN - Kristina Sulatri (JURNAL PENGABDIAN MANDIRI, 2025)
To achieve one of the national goals—namely, to educate the life of the nation as mandated in the fourth paragraph of the Constitution of the Republic of Indonesia of 1945—adequate Human Resources (HR) are required. To improve these human resources, the initial step is to cultivate reading interest from an early age. Indonesia's current PISA score ranks 70th out of 80 countries. This is certainly concerning, especially when linked to the effort to achieve the aforementioned national goal. Therefore, several initiatives are needed to address this issue. Fostering reading interest in children from an early age is intended to ensure that the ability to access and communicate information is ingrained early on. Thus, it is hoped that the foundation for educating children is established from a young age. The Literacy Corner created at PAUD Tunas Harapan in Warungdowo Village, Pohjentrek Subdistrict, Pasuruan Regency began by educating parents of students and educators at PAUD about the importance of reading and strategies to cultivate children's reading interest. For the children themselves, the method used involves games that introduce letters and numbers, as well as reading together. In this way, learning is expected to become something engaging and enjoyable for children.